Principal's Leadership Style In The Era Of Globalization In An Effort To Improve Teachers' Performance Teacher Performance at SMP Teuku Nyak Arif Fatih Bilingual School - Fakhri Fakhri; Khairuddin Khairuddin; Niswanto Niswanto (Asian Journal of Social and Humanities, 2024)
This study aims to 1) describe the development of the principal's leadership style in the era of globalization in an effort to improve teacher performance at Teuku Nyak Arif Fatih Bilingual School Banda Junior High School, 2) to find out the effectiveness of the development of a clear development of the leadership style of school leaders in the era of globalization in an effort to improve teacher performance at Teuku Nyak Arif Fatih Bilingual School Banda Aceh Junior High School, and 3) can evaluate the development of school leadership styles in the era of globalization in an effort to improve teacher performance at Teuku Nyak Arif Fatih Bilingual School Banda Aceh Junior High School. This research uses a qualitative approach and a descriptive method. The subjects of this study consist of principals, teachers, and administrative staff of Teuku Nyak Arif Fatih Bilingual School Banda Aceh Junior High School. Data collection techniques with observation, interviews and documentation studies. The data analysis techniques used are data reduction, data display and drawing conclusions. The results of this study are: 1) the development of the principal's leadership style in the era of globalization in an effort to improve teacher performance 2) the implementation of the role of the principal in an effort to improve teacher performance, so as to help foster an increase in the understanding of the school community in improving teacher performance and 3) the implementation of the principal's leadership in an effort to improve performance through the school and can foster the awareness of school residents on the importance of improving teachers' performance to be taught from an early age which will develop into a culture for them.